The memory of brazilians and guyaneses about the rupununi uprising in the frontier Brazil – Guyana - Pereira, Mariana Cunha (Textos e Debates, 2016)
In this text, I re-elaborate the narratives and oral speech of some of the social subjects (Guyanese Negroes, Macushi Indigenous and Wapishana, regional Brazilians) about the Rupununi Uprising. The narratives and oral speech of the interviewees on the subject are partially constituted by the fieldwork that originated the Ethnography built as a doctorate thesis in the frontier Brazil-Guyana. The intention is to contextualize, by means of these narratives, the realms of memory that make up the political landscape of the 60s in these two countries, since the political event called Rupununi Uprising, characterized as one of the most polemic period in Guyana’s history. In Brazil, milestones of this decade were the military dictatorship and the leftist movements.In Guyana it is a moment of the process of independence and of secession fights.